Penerapan Prinsip Kehati-hatian Pada Data Nasabah Pinjaman Secara Online - Metanila, Meyske Adriani; Pesulima, Theresia Louize; Pariela, Marselo Valentino Geovani (Faculty of Law, Universitas Pattimura, 2024)
Introduction: Process of providing loans without intermediaries such as banks and credit institutions, there is a special website in the form of an implementation platform where the user can become a giver. In online loans, some are guaranteed and some are without collateral, this can lead to misuse of personal data for users of financial technology services.Purposes of the Research: The purpose of writing this thesis is to find out and explain the application of the precautionary principle of online loan customer data and how the form of legal protection for online loan customer data.Methods of the Research: The research method used in this study is normative juridical with a conceptual approach and statutory regulations and legal materials used are primary and secondary legal materials.Results of the Research: The The results of this study indicate that financial technology is an innovation or a combination of conventional banking credit agreement systems with a touch of modern technology. The system for managing credit agreements in financial technology includes: Basic Banking Law No. 10 of 1998, Bank Indonesia Regulation (PBI) No. 19/12/PBI/2017 concerning the Implementation of Fintech, Financial Services Authority Regulation No. 77/POJK.01/2016 regarding Information Technology-Based Money Borrowing Services Digital Financial Services, then Regulations regarding the principle of prudence in fintech credit agreements have the same rights and obligations between conventional credit agreements with fintech.